Representasi Penerimaan Diri Kaum Wanita pada Vidio Tutur Batin - Bahar, Nisauzzahra; Sunarto, Sunarto; Nugroho, Adi (Interaksi Online, 2024)
The beauty of women in Indonesia is very diverse, but society has the view that the standard of beauty for women is white skin, slim, thin, no acne, straight hair, and must have body goals, which gives rise to body shaming, bullying, even infidelity and can cause mental health disorders. Music can be a creative means to express feelings of happiness or sadness. Tutur Batin by Yura Yunita tells about the life process of women with their own problems and how they can accept themselves. The object of this research is the representation of women's self acceptance in the song Tutur Batin. The researcher uses qualitative methods as a research approach and uses Paul Rice's text hermeneutics methodology. This research uses standpoint theory, representation, self-acceptance, radical feminism, music, new media, and filmic aspects. This research has three research processes through grammatical analysis, semantic analysis, and text interpretation. Research findings in the song Tutur Batin include four stages of disappointment, toughness, sincerity, and self-acceptance. The results of research into the representation of the song Tutur Batin are that the women in the song Tutur Batin are finally able to accept themselves through various problem processes. Then they remember that there are still people who care about them and they meet women who do not have appropriate beauty standards and they exchange stories so that it opens their minds that they have to love themselves with what they have and there are still people near them who still care about their situation, such as the siblings and children they have.